2000
DOI: 10.1093/carcin/21.4.691
|View full text |Cite
|
Sign up to set email alerts
|

Significant overexpression of metallothionein and cyclin D1 and apoptosis in the early process of rat urinary bladder carcinogenesis induced by treatment with N-butyl-N-(4-hydroxybutyl)nitrosamine or sodium L-ascorbate

Abstract: Effects of a genotoxic bladder carcinogen, N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN) and a non-genotoxic bladder promoter, sodium L-ascorbate (Na-AsA), on protein expression, cell proliferation and apoptosis of the bladder epithelium with or without the influence of testicular castration were investigated. Male F344 rats were divided into six groups (groups 1-6). BBN was given with 0.05% drinking water to groups 1 and 4 for 8 weeks, groups 2 and 5 received diet with 5% Na-AsA. Then the animals were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
3
15
0
1
Order By: Relevance
“…Between 0 and 3% of intensely stained nuclei were observed, mostly in the upper layer of normal and hyperplastic urothelia and in TCCs, as was reported by Takaba et al (16) in BBN-treated rat bladders. However, we found no difference in the proportion of apoptotic cells between wt and Ptc ϩ/Ϫ mice at any time (0.17 Ͻ P Ͻ 0.89; data not shown).…”
Section: Resultssupporting
confidence: 77%
“…Between 0 and 3% of intensely stained nuclei were observed, mostly in the upper layer of normal and hyperplastic urothelia and in TCCs, as was reported by Takaba et al (16) in BBN-treated rat bladders. However, we found no difference in the proportion of apoptotic cells between wt and Ptc ϩ/Ϫ mice at any time (0.17 Ͻ P Ͻ 0.89; data not shown).…”
Section: Resultssupporting
confidence: 77%
“…Metallothionein overexpression in ESCC is often positively correlated with the metastatic and proliferative activities of the cancer (36). In animal tumor models, overexpression of metallothionein has been shown in chemically induced rat and mouse bladder tumors (39,40). Our results show that metallothionein overexpression occurs in precancerous zinc-deficient esophagus (Tables 1 and 2; Fig.…”
Section: Discussionsupporting
confidence: 59%
“…This is consistent with the data reported previously. 37,[48][49][50][51][52] In this study, DITC effectively suppressed cyclin D1-positive cell ratios of urinary bladder, implying that reduction in the incidence of tumors and preneoplastic lesions of urinary bladder is related to effectively suppressed cell cycle progression by the treatment with DITC. In our recent study, another selective cyclin D1 inhibitor, silymarin have also been demonstrated to possess chemopreventive potential on BBN-induced urinary bladder carcinogenesis in male ICR mice.…”
Section: Discussionmentioning
confidence: 87%